Assessing teachers and peer teacher students’ perceptions of their motivations and participation impact in peer learning projects: the role of content analysis supported by WebQDA - Carvalho, Ana Raquel (2021)
According to literature review, the number of studies focusing on Computer-Assisted Qualitative-Data Analysis Software (CAQDAS) as well as on clear descriptions of how these tools can be used is still scarce. Besides this, despite the recognition of content analysis for its appropriateness to qualitative studies, several authors refer to ambiguity problems, mostly related to the subjec-tivity of the coding process, which may interfere with the assurance of the validi-ty criteria of stability, reproducibility and accuracy. Goals and methods: This study is predominately methodological and focuses on a segment of the results of a multiple case study, involving five peer learning projects, implemented in five Portuguese educational institutions; and on the re-flection on the role of content analysis, as the chosen data analysis technique, and the support of qualitative analysis software WebQDA, particularly regarding the assurance of the validity criteria of reproducibility and accuracy. By means of a semi-structured interview and a survey by questionnaire, this study aims at as-sessing teachers and peer teacher students’ perceptions of motivations to integrate the projects as well as of the contributions resulting from participation, regarding benefits and major challenges; and analyse the role of content analysis, supported by software WebQDA, in identifying these teachers and peer teacher students’ convergent/divergent perceptions. Results: Results show there is clear convergence of teachers and peer teacher students’ perceptions regarding the three variables assessed, particularly as for participation benefits. It is also evident that teachers and peer teacher students’ perceptions diverge in matters related to specificities of the role assumed in the projects. The contribution of software WebQDA was particularly significant re-garding the transparency, structure and systematization facilitated. Conclusions: Conclusions enhance the role of content analysis and of software WebQDA for promoting reflexive and in-depth analysis of the collected data and for assuring replication of the study.